Synthesis, tribology, electro-tribology and mechanical performance of ti2alc and ti3alc2 max phases thin films - Quispe Dominguez, Roger (2022)
This thesis investigates the synthesis, mechanical properties, tribological and electro-tribological behavior of Ti2AlC and Ti3AlC2 MAX phases in the form of thin films. The thin films were obtained by deposition of a multilayer system of Titanium (Ti) - Aluminum (Al) - Carbon (C) and subsequent thermal annealing in a vacuum and controlled atmosphere. The Ti-Al-C multilayer system was deposited by magnetron sputtering on silicon substrates with a SiO2 and SixNy double-layer diffusion barrier. The stoichiometric of the film was controlled through the thickness of the individual monolayers. To obtain a 500 nm thick film, the Ti-Al-C sequence was repeated 22 times with individual thicknesses of 14, 6 and 3.5 nm, respectively. The experimental results show that the Ti2AlC phase is formed at a temperature of 700°C, while the Ti3AlC2 phase is formed at 950°C. The structural properties of the thin films were characterized by X-ray diffraction, Raman microscopy and glow discharge optical emission spectroscopy (GD-OES). The hardness of the thin films was analyzed by nanoindentation tests, obtaining hardness values of 11.6 and 5.3 GPa for Ti2AlC and Ti3AlC2, respectively. The tribological behavior of the thin films was analyzed under dry sliding conditions using a ball-on-flat reciprocating tribometer. The counter body consisted of AISI 52100 steel balls of 3 mm diameter. The friction coefficients obtained were in the range of 0.21 - 0.2 and 0.6 - 0.91 for the Ti2AlC and Ti3AlC2 thin films, respectively. The Ti2AlC phase has a better tribological performance, which can be attributed to its smaller grain size, lower surface roughness and higher hardness compared to the Ti3AlC2 phase. The electrical resistivity of the thin films was 0.73 and 0.45 μΩ·m for Ti2AlC and Ti3AlC2, respectively. The electro-tribological test was carried out using a ball-on-flat reciprocating tribometer under electrical currents of 10, 50 and 100 mA. The coefficient of friction and the electrical contact resistance were measured simultaneously in the same test. The results show that the coefficient of friction and electrical contact resistance could be related to thin-film properties such as hardness, roughness, grain size, and resistivity. These results of the electro-tribological behavior of the films provide valuable information for possible applications such as sliding electrical contacts.